International aid and cyclone shelters in Bangladesh: adaptation or maladaptation? - Dhakal, Subas P.; Mahmood, M. (Routledge, 2014)
This paper examines the unintended prospect of international aid-driven maladaptation in Bangladesh. While attempts by aid agencies to channel scarce resources to finance structural adaptation measures are commendable, complementary non-structural measures remain under the radar. Using an exploratory research approach this paper investigates the state of cyclone shelters in two coastal districts: Chittagong and Cox’s Bazar. The findings indicate that the lack of adequate shelter capacity, maintenance funding, and community participation has exacerbated the vulnerability of Chittagong’s marginalised urban population. The paper contends that international aid can avoid being maladaptive by accentuating community-based governance and facilitating community capacity to fund the maintenance of cyclone shelters in new ways.